Hegel on history - McCarney, Joe (Routledge philosophy guidebooks., 2000)
Hegel's Introduction to the Philosophy of History remains one of the most profound and influential books on the philosophy of history. In clear and cogent terms this book:* examines the ideas and arguments of the Introduction to the Philosophy of History* explains key concepts of Hegel's system, a knowledge of which is essential for fully understanding his philosophy of history* assesses the continuing relevance of Hegel to the contemporary debate about the nature of history.